Disseminated cutaneous classical Kaposi’s sarcoma in a Polish man – case report - Żychowska, Magdalena; Batycka-Baran, Aleksandra; Baran, Wojciech; Maj, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Kaposi’s sarcoma is an angioproliferative neoplasm of four distinct clinical forms. The classical variant is mainly seen in males of Jewish or Mediterranean origin. Skin lesions are predominantly located on the lower limbs. The disease is characterized by a slow and indolent course. In most patients the lesions are limited to skin, and internal involvement is observed in 4-15% of cases. Objective . To present and discuss the classical variant of Kaposi's sarcoma and highlight therapeutic options. Case report . A 77-year-old man of Polish origin, with negative history of immunosuppressive therapy, presented with multiple disseminated red-to-purple nodules and plaques. Histopathological examination confirmed the diagnosis of Kaposi's sarcoma. HIV screening was negative. Conclusions . As classical Kaposi's sarcoma is characterized by an indolent course, systemic chemotherapy is not always required. Staging, internal involvement, complications, patient’s age and concomitant diseases should be taken into consideration when choosing the best therapeutic option.